2016
DOI: 10.1002/pchj.140
|View full text |Cite
|
Sign up to set email alerts
|

Developmental trajectory of time perspective: From children to older adults

Abstract: Time perspective is a fundamental dimension of the psychological time construct, with a pervasive and powerful influence on human behavior. However, the developmental trajectory of time perspective across a human lifespan remains unclear. The current study aimed to portray the developmental trajectory of all dimensions of time perspectives from children to older adults in a large sample. A total of 1,901 individuals (aged 9-84 years) completed measures of time perspective. They were then divided into five age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 47 publications
(96 reference statements)
0
8
0
Order By: Relevance
“…This syndrome, along with school participation, have been found to be the two factors involved in school wellbeing [ 16 , 17 ]. Furthermore, it means students have a more negative perspective of the future [ 18 ], and is a risk factor for developing behaviors such as smoking [ 19 ], altered sleep quality and symptoms of depression, anxiety and stress linked with negative affect [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This syndrome, along with school participation, have been found to be the two factors involved in school wellbeing [ 16 , 17 ]. Furthermore, it means students have a more negative perspective of the future [ 18 ], and is a risk factor for developing behaviors such as smoking [ 19 ], altered sleep quality and symptoms of depression, anxiety and stress linked with negative affect [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, oPN (1.95), oPP (4.60), oPF (1.50), oPH (3.90), oF (4.00) represent optimal scores of Past-Negative, Past-Positive, Present-Fatalistic, Present-Hedonistic, and Future TP, respectively, while ePN , ePP , ePF , ePH , eF represent scores of Past-Negative, Past-Positive, Present-Fatalistic, Present-Hedonistic, and Future TP reported by participants [ 31 ]. DBTP, calculated from the ZTPI, is viewed as the optimal indicator of balanced TP [ 32 ], and has been widely used in Chinese populations [ 5 , 9 , 18 , 33 ]. A lower DBTP score indicates a more balanced TP.…”
Section: Methodsmentioning
confidence: 99%
“…For the Past-Negative and Present-Fatalistic orientations, low values result in less perceived stress, whereas high values are associated with increased helplessness (Chen et al, 2016a(Chen et al, , 2016b, resulting in maladaptive stresscoping strategies and higher levels of emotional stress . Zajenkowski et al (2016) identified Present-Fatalistic and Past-Negative perspectives related to high stress levels.…”
Section: The Association Of Time Perspectives (Tps) On Self-efficacy ...mentioning
confidence: 99%
“…Consequently, we suggest the conduction of longitudinal studies, in order to better understand how TP and burnout proneness are related to each other and to further scrutinize our hypotheses. Several authors issued the change of TPs along the life span (Chen et al, 2016a(Chen et al, , 2016bLaureiro-Martinez et al, 2017). It is assumed that TPs are developed during socialization, and that during each phase of life, shifts and alterations are possible and can be expected.…”
Section: Limitations and Future Researchmentioning
confidence: 99%